Language as a creator of realities and public opinion: Critical analysis in the context of the current media ecosystem - Civila, Sabina (2020)
This article analyzes how the media constructs social reality through language. Social reality is revised as a discursive construct based on the anthropic principle of information and on Watzlawick's axiom that, “it is impossible not to communicate”. The main objective is to analyze how the concept of “public opinion” has evolved with the development of Information and Communications Technologies (ICT). To this end, a critical review of scientific literature has been carried out, mapping the WoS and Scopus databases, and determining, through a literature review, how the new definitions of public opinion are formed. This increases the understanding of the media ecosystem and the interactions of individuals at the digital communication level. The main conclusion of this study highlights how public opinion is no longer created unidirectionally and monopolistically through conventional media, but with the interaction and participation of the “prosumer audience” within social networks. However, this does not mean the role of the media in social control has been completely lost through strategies such as framing and priming. Indeed, new informative vices, such as fake news, have emerged from this interactive construction of realities.